Comparison of the effect of Haas and Hyrax rapid palatal expanders on nasal cavity dimensions - Amini F.; Ramezanei GH (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: In treatment of posterior crossbite awareness of the effects of Haas and Hyrax rapid maxillary expanders (RME) on nasal cavity will help the clinician to select the better appliance. This study was carried out to compare the effects of Haas and Hyrax expanders on the nasal cavity of patients treated for posterior crossbite. "nMaterials and Methods: A clinical trial study was designed on posteroanterior (PA) cephalograms of 30 subjects to evaluate the nasal cavity width of 14 subjects (8 female & 6 male) with mean chronological age of 12± 2years who received RME with Hyrax type and 16 subjects (9 female & 7 male) with mean chronological age of 11±1.6 years who received Haas type palatal expander. Paired t-test was used to analyze the outcomes of expansion in each group. Student t-test was used to compare Haas and Hyrax groups. "nResults: The mean value of screw expansion was 9±2 mm in both groups. In Hyrax group nasal cavity width"n(Nc-cN) increased from 29.2 ±1.94 mm to 31.7 ±1.93mm (p= 0.001) and In Haas group it was increased from 27.75± 2.21 mm to 29.35 ± 2.26 mm(p= 0.043). When two groups were compared to each other, statistically this increase was more significant in Hyrax than in the Haas group (p=0.038). "nConclusion: In this study RME affected geometry of the nasal cavity by increasing the nasal cavity width. However In our sample, Hyrax appliance demonstrated better performance over the Haas appliance in all variables.